2009
DOI: 10.1158/1078-0432.ccr-08-2283
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Her-2/neu Chimeric Molecule Expressed byListeria monocytogenesCan Elicit Potent HLA-A2 Restricted CD8-positive T cell Responses and Impact the Growth and Spread of Her-2/neu-positive Breast Tumors

Abstract: Purpose: The aim of this study was to efficiently design a novel vaccine for human Her-2/ neu-positive (hHer-2/neu) breast cancer using the live, attenuated bacterial vector Listeria monocytogenes. Experimental Design:Three recombinant L. monocytogenes^based vaccines were generated that could express and secrete extracellular and intracellular fragments of the hHer-2/neu protein.In addition, we generated a fourth construct fusing selected portions of each individual fragment that contained most of the human le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…3 In the first approaches to target the HER2/neu antigen using Listeria monocytogenes (Lm), Listeria-based vaccines expressing small fragments of the extra and intracellular domains of the rat and human HER2/neu protein were constructed. 4,5 We also generated a Listeria vaccine (Lm-LLO-ChHer2) using a chimeric protein by fusing two of the extracellular and one intracellular fragments of the human HER2/neu, including most of the known major histocompatibility complex (MHC) class I epitopes of the protein. 5 All of these vaccines were shown to be immunogenic and efficacious in regressing preestablished tumors in FVB/N mice and delay the onset of spontaneous mammary tumors in HER2/neu-expressing transgenic animals.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 In the first approaches to target the HER2/neu antigen using Listeria monocytogenes (Lm), Listeria-based vaccines expressing small fragments of the extra and intracellular domains of the rat and human HER2/neu protein were constructed. 4,5 We also generated a Listeria vaccine (Lm-LLO-ChHer2) using a chimeric protein by fusing two of the extracellular and one intracellular fragments of the human HER2/neu, including most of the known major histocompatibility complex (MHC) class I epitopes of the protein. 5 All of these vaccines were shown to be immunogenic and efficacious in regressing preestablished tumors in FVB/N mice and delay the onset of spontaneous mammary tumors in HER2/neu-expressing transgenic animals.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 We also generated a Listeria vaccine (Lm-LLO-ChHer2) using a chimeric protein by fusing two of the extracellular and one intracellular fragments of the human HER2/neu, including most of the known major histocompatibility complex (MHC) class I epitopes of the protein. 5 All of these vaccines were shown to be immunogenic and efficacious in regressing preestablished tumors in FVB/N mice and delay the onset of spontaneous mammary tumors in HER2/neu-expressing transgenic animals. 5 Because of the high homology (B96%) between rat and human HER2/neu protein sequences and at least three known common H-2D q epitopes between the two proteins, these preliminary experiments suggested that Lm-LLO-ChHer2 could break the tolerance toward the HER2/neu self-antigen.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations